PENGARUH TIME DEMANDS OF WORK TERHADAP KEPUASAN KERJA, STRESS KERJA, DAN TURNOVER INTENTION KARYAWAN (Studi Pada Karyawan PT. Bank Tabungan Negara (Persero) Tbk. Cabang Harapan Indah, Bekasi) - Hasanah, Anisah Uswatun (JURNAL STUDI MANAJEMEN ORGANISASI, 2016)
The aim of this research is to analyze the impact time demands of work, on job satisfaction,job stress, and employee turnover intention PT. Bank Tabungan Negara (Persero) Tbk.Cabang Harapan Indah, BekasiThis study is using path analysis with SmartPLS 2.0.M3. The population that used in thestudy is all the employees of PT. Bank Tabungan Negara (Persero) Tbk. Cabang HarapanIndah, Bekasi, which are 108 respondents. The amount of the sample is determined by thecensus method of the entire employee. However the sample that has been applied into 85respondents significantly decreased into 85people.The results have shown that the time demands of work do not significantly influenceturnover intention. Furthermore the time demands of work have no significant effect on jobsatisfaction. Employee satisfaction negatively affect on turnover intention. Job satisfactionis not successfully mediating the relationship between the time demands of work andturnover intention. Time demands of work have positive influence on job stress. Job stresshas positive effect on turnover intention. Job stress has been successfully mediating therelationship between the time demands of work and turnover intention. Job stressnegatively affect with job satisfaction. Job satisfaction also has been successfullymediating the relationship between job stress and turnover intention.